2021
DOI: 10.1245/s10434-021-10734-3
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Related Prognostic Factors for Anastomotic Leakage, Major Complications, and Short-Term Mortality Following Esophagectomy for Cancer: A Systematic Review and Meta-Analyses

Abstract: Objective The aim of this study is to identify preoperative patient-related prognostic factors for anastomotic leakage, mortality, and major complications in patients undergoing oncological esophagectomy. Background Esophagectomy is a high-risk procedure with an incidence of major complications around 25% and short-term mortality around 4%. Methods We systematically searched the Medline and Embase databases for stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 80 publications
3
20
0
Order By: Relevance
“…In line with current literature, our study has demonstrated that ASA score ≥III is associated with anastomotic leakage and pulmonary complications 17,19 . Both patients with advanced age and high ASA classification are thought to have lower healing capacity causing higher susceptibility to postoperative complications.…”
Section: Discussionsupporting
confidence: 88%
“…In line with current literature, our study has demonstrated that ASA score ≥III is associated with anastomotic leakage and pulmonary complications 17,19 . Both patients with advanced age and high ASA classification are thought to have lower healing capacity causing higher susceptibility to postoperative complications.…”
Section: Discussionsupporting
confidence: 88%
“…Another concern is the objective assessment of the postoperative complications, which remained scarce until recently (i.e., anastomotic leak, pulmonary complications). Lately, this has been addressed and refined through benchmarking and audits originating from high-volume centers and experts in the field [39][40][41]. Therefore, the implementation of common tools and strategies in the assessment of the postoperative results among the different centers can now be pursued and achieved.…”
Section: Discussionmentioning
confidence: 99%
“…24 Each patient's unique profile of comorbidities must also be evaluated, but few are absolute contraindications to esophagectomy. Cardiorespiratory disease, 25 liver cirrhosis, 26,27 renal failure, 28,29 and diabetes 30 are examples of comorbidities that are associated with increased perioperative risk in esophagectomy but can be managed in select patients to permit safe surgery. In addition, patient anatomy, past history of surgery and radiation may have a major impact on the complexity of esophagectomy surgery and reconstruction.…”
Section: High-risk Patientsmentioning
confidence: 99%